1982
DOI: 10.1002/actp.1982.010330705
|View full text |Cite
|
Sign up to set email alerts
|

A possibility of observing the structure forming process in polypropylene crystallization

Abstract: The existence of the specific metastable phase made it possible to carry out multistage electron microscopic investigation of the supermolecular structure formation in the crystallization of polypropylene in the oriented state. Comparison with the data of electron diffraction yielded a direct evidence of the fact that the formation of structural units of the supermolecular organization of crystalline PP, i.e. fibrils and lamellae, occurs in the stage of orientation, and crystallization itself oiily fixes these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Grosskurth 4 concluded that its morphology depends on the degree of molecule orientation but is independent of the method of orientation. Bezruk et al 5 pointed out that the morphological changes of PMMA films are similar to those of amorphous-crystal polymers during the uniaxial elongation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Grosskurth 4 concluded that its morphology depends on the degree of molecule orientation but is independent of the method of orientation. Bezruk et al 5 pointed out that the morphological changes of PMMA films are similar to those of amorphous-crystal polymers during the uniaxial elongation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a number of techniques have been used to investigate the structural changes of amorphous polymers during drawing process. These include WAXD, 2,3 electron microscopy, 4,5 etc.…”
Section: Introductionmentioning
confidence: 99%
“…Grosskurth4 concluded that its morphology depends on the degree of molecule orientation but is independent of the method of orientation. Bezruk et al5 pointed out that the morphological changes of PMMA films are similar to those of amorphous‐crystal polymers during the uniaxial elongation.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a number of techniques have been used to investigate the structural changes of amorphous polymers during drawing process. These include WAXD,2, 3 electron microscopy,4, 5 etc.…”
Section: Introductionmentioning
confidence: 99%